The burden of the past history, memory, and identity in contemporary Ukraine - Wylegała, Anna 1982-; Głowacka-Grajper, Małgorzata 1976- (Indiana University Press, 2020)
Cover -- Title Page -- Copyright -- Contents -- Note on Transliteration -- List of Abbreviations -- Introduction / Anna Wylegała and Małgorzata Głowacka-Grajper -- Part I. The Memory of Holodomor -- 1. Idle, Drunk, and Good for Nothing: Cultural Memory of the Rank-and-File Perpetrators of the 1932-33 Famine in Ukraine / Daria Mattingly -- 2. The Lieux de Mémoire of the Holodomor in the Cultural Landscape of Modern Ukraine / Wiktoria Kudela-Świątek -- Part II. World War II in the Ukrainian Memory -- 3. The War of Memory in Times of War: May 9 Celebrations in Kyiv in 2014-15 / Tetiana Pastushenko -- 4. (In)different Memory: World War II in the Memory of the Last War's Generation in Ukraine / Mykola Borovyk -- Part III. Heroes or Traitors: Creating a Heroic Canon -- 5. Symon Petliura, the Ukrainian People's Republic, and National Commemoration in Contemporary Ukraine / Matthew D. Pauly -- 6. Glory to the Heroes? Gender, Nationalism, and Memory /Olesya Khromeychuk -- Part IV. Traces of the Lost Multiethnicity and Memory of the Ethnic Cleansing -- 7. Memory, Monuments, and the Project of Nationalization in Ukraine: The Case of Chernivtsi / Karolina Koziura -- 8. Collective Memory of the Holocaust in Post-Soviet Ukraine / Anna Chebotarova -- 9. Extermination of the Roma in Transnistria during World War II: Construction of the Roma Collective Memory / Anna Abakunova -- 10. Poland and Poles in the Collective Memory of Galician Ukrainians /Anna Wylegała -- Part V. History and Politics in a Post-Soviet State: Ukraine, Russia, and Independence -- 11. Ukraine between the European Union and Russia since 1991: Does It Have to Be a Battlefield of Memories? / Tomasz Stryjek -- 12. A Desired but Unexpected State: The 1990s in the Memory and Perception of Ukrainians in the 21st Century / Joanna Konieczna-Sałamatin -- Index.